Kepuasan Konsumen Produk Sokasi Desa Kayubihi Ditinjau dari Kualitas Produk dan Harga - Telaga, Ni Made Pratiwi (Jurnal Pendidikan Ekonomi Undiksha, 2022)
This study aims to determine the effect of product quality and price on consumer satisfaction on the products of Sokasi Desa Kayubihi. The research design used is causal quantitative research. The subjects of this research are consumers of products in Sokasi Kayubihi Village. The sampling technique used is non-probability sampling with purposive method sampling and set a sample of 75 respondents. The analytical method used is multiple linear regression analysis with the analysis tool Statistical Package for Social Science (SPSS). The results showed that product quality and price together had a significant effect on consumer satisfaction with a contribution of 71.7%. In addition, product quality can also partially increase consumer satisfaction on the products of Sokasi Kayubihi Village with a contribution of 16.6% influence. Likewise, the price partially has a positive influence on consumer satisfaction on the product Sokasi Kayubihi Village with a contribution of 21.1% influence. Therefore, improving product quality and setting appropriate prices can increase consumer satisfaction with products Sokasi Kayubihi Village.